Effectiveness of Team Building Training Improving The Cohesiveness of The Working Group - Wildan Sidiq; Sri Muliati Abdullah (Psikostudia : Jurnal Psikologi, 2022)
The study aims to test the effect of team building training on the cohesiveness of working groups on production operators on CV. The subject of this study was the employees of production operators who had a low level of cohesiveness. The research method is an experiment with the type "Nonequivalent control group design", where 21 study subjects are divided into 11 experimental groups and 10 control groups. The interventions used were team building training given to the experimental group, while the control group was not given any intervention. The data analysis technique used Mann Whitney to determine the difference in the average group of experiments with the control group. The results revealed that team building training can improve group cohesiveness to be higher with a significant score difference (p < 0.05). The results of this study can be used as a reference to establish team building training programs regularly and periodically so that the company is able to maintain group cohesiveness in its working group. Penelitian ini bertujuan untuk menguji pengaruh pelatihan team building terhadap kohesivitas kelompok kerja pada operator produksi di CV. IM. Subjek penelitian ini ialah karyawan operator produksi yang memiliki tingkat kohesivitas rendah. Metode penelitian ialah eksperimen dengan jenis “Nonequivalent control group design”, dimana 21 orang subjek penelitian dibagi menjadi 11 orang kelompok eksperimen dan 10 orang kelompok kontrol. Intervensi yang digunakan ialah pelatihan team building yang diberikan kepada kelompok eksperimen, sedangkan kelompok kontrol tidak diberikan intervensi apapun. Teknik analisis data menggunakan Mann Witney untuk mengetahui perbedaan rata-rata kelompok eksperimen dengan kelompok kontrol. Hasil penelitian mengungkapkan bahwa pelatihan team building dapat meningkatkan kohesivitas kelompok menjadi lebih tinggi dengan perbedaan skor yang signifikan (p < 0,05). Hasil penelitian ini dapat dijadikan rujukan untuk menetapkan program pelatihan team building secara rutin dan berkala agar perusahaan mampu mempertahankan kohesivitas kelompok pada kelompok kerja yang dimilikinya.